Revisiting actors’ role in circular economy governance: A case of electric vehicle waste batteries in South Korea - Lee, Youhyun; Kim, Minjeong; Kim, Kyoungmin (Environmental Engineering Research, 2024)
An increase in the number of electric vehicle (EV) waste batteries has driven the growth of the waste battery market. In the EV battery industry, South Korea has demonstrated excellent output in battery production but poor output in waste battery reuse and recycling. To determine appropriate waste battery use, primary governance actors should establish their role and lead the early stage of the industrial ecosystem. Herein, we elucidated the appropriate role of each circular governance actor in EV waste batteries using the South Korean case. We used the analytic hierarchy process, a semiquantitative method, and included 37 circular economy experts. For the first class, the firm is the most important actor in the circular governance of waste batteries, with a weight of 0.404, followed by the central (0.375) and local (0.221) governments. For the second class, the reuse industry (0.167) requires more attention than the recycling industry (0.133). Because many countries worldwide interested in the waste battery market have yet to begin the implementation stage, analyzing South Korea’s case can offer practical insights for countries aiming to expand their waste battery market with a clear policy orientation towards carbon neutrality or net-zero emissions and strong policy actor leadership.
Keywords: Battery industry; Battery markets; Battery production; Circular economy; Electric vehicle batteries; Governance; Industrial ecosystems; Reuse and recycling; South Korea; Waste batteries; Circular economy; Electric vehicles; Governance; Waste batteries